Use of continuous glucose monitoring in obesity research: A scoping review. Issue 5 (September 2021) - Hegedus, Elizabeth; Salvy, Sarah-Jeanne; Wee, Choo Phei; Naguib, Monica; Raymond, Jennifer K.; Fox, D. Steven; Vidmar, Alaina P.
Highlights: Continuous glucose monitoring is tolerated in obesity research. Standard deviation is the most common glycemic variability metric. Continuous glucose monitoring can provide biofeedback and monitor dietary adherence. Abstract: Background: This scoping review provides a timely synthesis of the use of continuous glucose monitoring in obesity research with considerations to adherence to continuous glucose monitor devices and metrics most frequently reported. Methods: This scoping review was conducted adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) checklist. Eligible studies (n = 31) evaluated continuous glucose monitor use in research on participants, of all ages, with overweight or obesity. Results: Reviewed studies varied in duration from one to 84 days (mean: 8.74 d, SD 15.2, range 1–84 d) with 889 participants total (range: 11–118 participants). Across all studies, the mean percent continuous glucose monitor wear time (actual/intended wear time in days) was 92% (numerator – mean: 266.1 d, SD: 452, range: 9–1596 d/denominator – mean: 271.6 d, SD: 451.5, range: 9–1596 d). Continuous glucose monitoring was utilized to provide biofeedback (n = 2, 6%), monitor dietary adherence (n = 2, 6%), and assess glycemic variability (n = 29, 93%). The most common variability metrics reported were standard deviation (n = 19, 62%), area under the curve (n = 12, 39%), and glycemic range (n = 12, 39%). Conclusions: Available evidence suggests that continuous glucose monitoring is a well-tolerated and versatile tool for obesity research in pediatric and adult patients. Future investigation is needed to substantiate the feasibility and utility of continuous glucose monitors in obesity research and maximize comparability across studies.